Clickable trimethylguanosine cap analogs modified within the triphosphate bridge: synthesis, conjugation to RNA and susceptibility to degradation. Issue 10 (20th January 2016) - Wojtczak, Blazej A.; Warminski, Marcin; Kowalska, Joanna; Lukaszewicz, Maciej; Honcharenko, Malgorzata; Smith, C. I. Edvard; Strömberg, Roger; Darzynkiewicz, Edward; Jemielity, Jacek
Abstract : Phosphate-modified m3 G cap analogs were synthesized, conjugated to RNA using "click chemistry", and studied for susceptibility to hNUDT16 enzyme. Abstract : The trimethylguanosine (m3 G) cap present at the 5′ end of small nuclear RNAs (snRNAs) has been proposed as an effective nuclear localization signal (NLS) for nucleus-targeting therapeutics such as antisense oligonucleotides. To provide novel tools for studies on m3 G-mediated transport and m3 G degradation, we synthesized a series of novel m3 G cap analogs that combine modifications potentially affecting its activity as an NLS and stability in vivo with a modification enabling simple conjugation to biomolecules. The synthesized dinucleotide m3 G analogs carry a single phosphate-modification (phosphorothioate, methylenebisphosphonate or imidodiphosphate) at the selected position of the triphosphate bridge in order to increase their resistance to enzymatic cleavage and a (2-azidoethyl)-carbamoylmethyl group at the 2′-position of adenosine as a second nucleotide to enable conjugation to alkyne-containing biomolecules by copper catalyzed azide–alkyne cycloaddition (CuAAC). The susceptibility of m3 G cap analogs to non-specific and specific degradation was studied in fetal bovine serum and in an in vitro decapping assay with hNUDT16 enzyme, respectively. The susceptibility of m3 G cap analogs to hNUDT16 mediated decapping was also determined after their CuAAC-mediated conjugation to a model oligonucleotide bearing a 5′-alkyne group. Depending on the type and the position of introduced modifications, they modulate the susceptibility to specific and non-specific degradation of conjugated molecules to various extent, with O to NH substitution at the α/β position providing the greatest m3 G stability against hNUDT16.